Role play to develop oral production of the English language in undergraduate engineering students - Reyes Carrasco, Rubén Orlando (2019)
This research aimed to develop the oral production of the English language in undergraduate engineering students at a national university. It was based on the need to improve the teaching of oral language production to promote oral ability in students. The research is interpretive paradigm educational. The sample consisted of four teachers and 26 students. Questionnaires and observation were used to collect data in this study. The information was processed and analyzed qualitatively and quantitatively, which allowed the generation of emerging categories. The diagnosis showed that teachers apply strategies that do not promote oral production in students or are contextualized. It is concluded that the scientific contribution of research is the design of the didactic strategy, based on the role play, which will generate a more interactive, contextualized and reflective teaching-learning process.